2018
DOI: 10.1186/s12913-018-3441-y
|View full text |Cite
|
Sign up to set email alerts
|

Board certification and urban–rural migration of physicians in Japan

Abstract: BackgroundThe board certification system serves as a quality assurance system for physicians, and its design and operation are important health policy issues. In Japan, board certification was established and operated independently by academic societies and has not been directly linked to reimbursement systems. The phenomenon of younger physicians seeking specialist careers has raised concerns about acceleration of the tendency of fewer physicians working in rural areas and the maldistribution of physicians. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Previous studies have indicated that the urban-rural dichotomy tends to play a part in the development of occupational burnout. 37,38…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that the urban-rural dichotomy tends to play a part in the development of occupational burnout. 37,38…”
Section: Discussionmentioning
confidence: 99%
“…Many Japanese physicians have attempted to obtain board certification, although this does not increase medical fees in Japan’s health insurance system. Newly board-certified physicians in rural and intermediate municipalities are likely to migrate to urban municipalities [ 8 ]; however, the participants in this study were all physicians, including those with specialties unsuitable for rural areas, and the follow-up period was only two years. To increase the number of rural physicians, the regional quota program at medical schools began in 2008, and medical students who take exams through the regional quota program and receive student loans, are obliged to work for the prefecture for nine years instead of exempting repayment [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Through the process of urbanization, people in Japan-especially the younger generation-have moved to the large cities, leaving rural areas with smaller populations and a higher proportion of residents who are older adults [11]. This situation has driven an unequal distribution of physicians, as well as other health care service providers [12,13]. Fewer facilities, less human resources, and greater di culty in accessing health care services have compromised people's health in rural areas of Japan.…”
Section: Introductionmentioning
confidence: 99%